Factors Affecting the Level of Public Confidence of Political Parties in the European Union - F. I. Dolgikh (Сравнительная политика)
Since the second half of the XX century, political parties as a socio-political institution were in a state of global crisis, the manifestations of which were the decline in the number of their members and the fall in the level of trust in them. The study aims to analyze the factors affecting the level of trust in political parties in the European Union; the objective -to identify these factors and determine the correlation between them and the level of trust in political parties. In this study, the level of confidence in the national government, the national Parliament, regional and local authorities, as well as levels of economic development and corruption, are considered as indicators correlating with the level of confidence in parties on a pan-European scale.The study is based on comparative and statistical methods. The source of the analysis is the data of sociological surveys on trust in political parties published on the official website of the European Commission on the results of population surveys in the framework of the “Eurobarometer” study for the period from 2000 to the present. The dependent variable is the level of trust in political parties, determined as a percentage of the number of respondents who trust this social institution.The analysis suggests that the lowest level of trust in political parties is typical for countries that have a low level of trust in the national government and Parliament, regional and local authorities, as well as for states where non-democratic regimes have existed for a long time. In addition, the level of trust in political parties correlates with the level of corruption in General and corruption of political parties in particular, and with the level of economic development, but the degree of their correlation is lower compared to other indicators considered. The level of trust in political parties below the Central European level is typical mainly for countries that have recently embarked on the path of democracy - the Baltic States, Eastern and Southern Europe.